1985
DOI: 10.1080/00222895.1985.10735338
|View full text |Cite
|
Sign up to set email alerts
|

Fitts’ Law in Two Dimensions with Hand and Head Movements Movements

Abstract: Subjects performed two-dimensional discrete movements either with a helmet-mounted sight or with a joystick. Fitts' Law was found to be a good predictor of the speed-accuracy tradeoff for both systems. The joystick produced faster movement times than the helmet-mounted sight. For both systems, horizontal and vertical movements were slightly faster than diagonal movements. Two dimensional generalizations of Fitts' Law were discussed in terms of multidimensional scaling. The obtained pattern of movement times wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
4

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 20 publications
10
99
2
4
Order By: Relevance
“…4 (cf., e.g., Jagacinski & Monk, 1985;MacKenzie, 1989MacKenzie, , 1992Boritz et al, 1991;Murata, 1996). Jagacinski and Monk (1985) and Boritz et al (1991) investigated how directional mouse movement affected pointing time and showed that the pointing times differed significantly across conditions of directional movement. In these studies, however, the performance modeling was conducted by pooling all directional mouse movements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 (cf., e.g., Jagacinski & Monk, 1985;MacKenzie, 1989MacKenzie, , 1992Boritz et al, 1991;Murata, 1996). Jagacinski and Monk (1985) and Boritz et al (1991) investigated how directional mouse movement affected pointing time and showed that the pointing times differed significantly across conditions of directional movement. In these studies, however, the performance modeling was conducted by pooling all directional mouse movements.…”
Section: Discussionmentioning
confidence: 99%
“…Although movement direction has some effects on the movement time in two-dimensional tasks (Boritz et al, 1991;Jagacinski & Monk, 1985), there are few explicit models that take these effects into account. However, movement direction seems to be an important factor in performance modeling, especially the modeling of three-dimensional pointing tasks.…”
Section: Extending Fitts' Law To a Three-dimensional Pointing Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…A threshold of 10° off-center was used for head orientation to allow for the few degrees of natural drift that has been observed while individuals attempt to hold their head motionless [20]. The threshold for EMG command onset was fixed at 20 percent of the EMG mvc and included a shifting baseline calculation to account for long-period changes in EMG magnitudes over the course of the experiment.…”
Section: Velocity Algorithmmentioning
confidence: 99%
“…However, few computer interfaces applicable to individuals with SCI have been similarly quantified. Headcommanded cursor position control has been investigated by Jagacinski and Monk [20], Radwin et al [21], and LoPresti et al [22][23], with performance assessed using a two-dimensional target-acquisition task similar to the one used in this study. Other than these, rigorous quantitative analysis of computer interfaces specifically applicable to individuals with SCI has not been performed.…”
Section: Introductionmentioning
confidence: 99%